Are institutional blockholders effective monitors? Evidence from corporate investment efficiency - Barka, Zeineb; Boubaker, Sabri; Hamza, Taher (Management international / International Management / Gestiòn Internacional, 2025)
This paper investigates the relationship between institutional blockholdings and corporate investment efficiency. Using a sample of 283 French-listed firms during 2002-2016, we find that institutional blockholders improve investment efficiency and decrease the magnitude of over-investment. This finding withstands a battery of sensitivity checks and remains unchanged after accounting for endogeneity concerns. Moreover, we provide evidence that investment inefficiency decrease in the presence of institutional investors with longer-term investment horizons due to improved monitoring and information quality. Third, we find that both foreign and domestic institutional blockholders play a significant role in shaping firms' efficient investment behavior. Finally, cross-sectional tests indicate that institutional monitoring mitigates investment distortions to a greater extent for firms facing higher agency problems and greater information asymmetry.